2023
DOI: 10.3390/cells12091234
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay between Oxidative Stress and the Nuclear Lamina Contributes to Laminopathies and Age-Related Diseases

Abstract: Oxidative stress is a physiological condition that arises when there is an imbalance between the production of reactive oxygen species (ROS) and the ability of cells to neutralize them. ROS can damage cellular macromolecules, including lipids, proteins, and DNA, leading to cellular senescence and physiological aging. The nuclear lamina (NL) is a meshwork of intermediate filaments that provides structural support to the nucleus and plays crucial roles in various nuclear functions, such as DNA replication and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 91 publications
0
6
0
Order By: Relevance
“…226 Not only is Nrf2 expression downregulated, but the protein is also sequestered by progerin, minimizing the amount of active Nrf2 to induce target genes. 226 Decreased expression of the lysophosphatidic acid receptor (LPA 3 ) also increases the level of ROS in HGPS model cells. 227 ROS links mutant lamins to other organellar dysfunction in laminopathies.…”
Section: Oxidative Stressmentioning
confidence: 99%
See 4 more Smart Citations
“…226 Not only is Nrf2 expression downregulated, but the protein is also sequestered by progerin, minimizing the amount of active Nrf2 to induce target genes. 226 Decreased expression of the lysophosphatidic acid receptor (LPA 3 ) also increases the level of ROS in HGPS model cells. 227 ROS links mutant lamins to other organellar dysfunction in laminopathies.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…However, a contradictory study reported that the level and function of superoxide dismutase (SOD1), CAT, and GSH are increased to the challenges of ROS in laminopathic cells expressing LMNA Y259X . 226 ROS also inhibits the transport of proteins from the cytosol to the nucleus by preventing the activity of RAN in HGPS cells. 230 Hydrogen sulphide (H 2 S) is another modulator of chromatin binding to nuclear lamina.…”
Section: Oxidative Stressmentioning
confidence: 99%
See 3 more Smart Citations